BASIS AND RECOMMENDATIONS OF CARDIOVASCULAR CONDITIONING - SANDHYA GUPTA,; SEEMA KUMAR,; SUSHIL DOHARE, (International Journal of Pharma and Bio Sciences, 2013)
Aerobic training induces functional and dimensional changes in cardio vascular system, referred to as cardio-vascular conditioning. This article attempts to give the physiological basis of the changes that occur in CVS conditioning. The changes include a decrease in resting heart rate, enhanced stroke volume, enhanced cardiac output and an expanded atrio-venous O2 difference. The major factors that affect training improvement are initial fitness level, frequency, intensity &duration of exercise; and the type (mode) of training. Exercise need not be strenuous to obtain positive training adaptations. An exercise heart rate of 70% maximum represents moderate exercise with little or no discomfort.